Hemodynamic Comparison of Two Nasal Endotracheal Intubation Techniques Using Fiberoptic and Conventional Approaches in Jaw Fracture Surgery Patients: A Study from Kerman, Iran (2020) - Naeimi Bafghi, Naeimeh; Salagegheh, Shirin; Salehi, Jafar; Naeimi Bafghi, Neda; Tajaddini, Mahdieh (Galen Medical Journal, 2024)
Background: Laryngoscopy and endotracheal intubation can cause significant hemodynamic changes, resulting in potentially life-threatening complications. This study aimed to compare the hemodynamic effects of traditional endotracheal tube and fiberoptic bronchoscope methods in patients undergoing maxillofacial fracture surgery. Materials and Methods: In this randomized clinical trial, 60 patients with jaw fractures at an institutional tertiary hospital in Kerman, Iran, in 2020 were enrolled. Participants were randomly assigned to either the traditional endotracheal tube group (n=30) or the fiberoptic bronchoscope group (n=30). Hemodynamic parameters, including systolic and diastolic blood pressure, heart rate, and arterial oxygen saturation (SpO2), were recorded at baseline, and 1, 3, 5, 10, and 15 minutes after anesthesia. Additional assessments included time to peak blood pressure, frequency of SpO2 drop, and postoperative nausea, vomiting, and hoarseness. Results: There were significant differences in systolic, diastolic, and mean arterial blood pressures, as well as heart rate, between the two groups (p < 0.05). The highest hemodynamic values occurred 3 minutes after anesthesia in the traditional intubation group and immediately after intubation in the fiberoptic group. SpO2 levels remained stable at 99% throughout the study in both groups. Hemodynamic values declined by the 10th and 15th minutes post-anesthesia. The study reveals that fiberoptic intubation is associated with lower early hemodynamic fluctuations compared to traditional intubation. This is particularly important as it suggests that fiberoptic intubation may mitigate the risk of cardiovascular complications, which can be life-threatening in vulnerable patient populations. Conclusion: Fiberoptic intubation resulted in lower early hemodynamic fluctuations compared to the traditional method, suggesting it may be a safer option for reducing cardiovascular stress during maxillofacial surgery. The current article presents a novel comparison of hemodynamic effects between traditional endotracheal intubation and fiberoptic bronchoscope methods specifically in the context of maxillofacial fracture surgery.